Investigating the role of three screening measures to support clinical decision-making in adult autism assessments - Janine Robinson; Carrie Allison; Bonnie Auyeung; Isabel C. H. Clare; Michael Lombardo; Navneet Nagra; Simon Baron-Cohen (PLoS ONE, 2025)
Referrals for autism diagnostic assessments in adults are increasing, with demand creating long waiting lists. Rigorously evaluated screening tools could serve to identify who is most likely to receive an autism diagnosis and contribute to clinical decision-making. We retrospectively examined individuals attending a specialist diagnostic assessment service in the UK over four years (2011–2014). Complete data on three screening measures were available for N = 422 referrals. These were the Autism Spectrum Quotient (AQ), the Empathy Quotient (EQ) and the Childhood Autism Spectrum Test–Relatives’ Questionnaire (CAST-RQ). 89% (n = 376) received an autism diagnosis. Positive screens on all three measures had a 98.3% likelihood of receiving an autism diagnosis, confirming findings from an independent clinic sample. We also examined the AQ subscale scores to establish their association with diagnostic outcome. While all people accepted onto the diagnostic assessment pathway should be offered an assessment, people who meet all three cut-offs could be offered a briefer assessment given the high likelihood that an autism diagnosis will be confirmed. Such triaging may lead to more efficient use of clinic time allowing referred individuals to be seen more quickly.